Specific Immune Responses and Oncolytic Effects Induced by EBV LMP2A-Armed Modified Ankara-Vaccinia Virus Vectored Vaccines in Nasopharyngeal Cancer - Liying Sun; Chao Liu; Junping Peng (Pharmaceutics)
Background: The Epstein-Barr virus (EBV) is intricately linked to a range of human malignancies, with EBV latent membrane protein 2A (LMP2A) emerging as a potential target antigen for immunotherapeutic strategies in the treatment of nasopharyngeal carcinoma (NPC). Methods: The modified vaccinia virus Ankara (MVA) is universally used in vector vaccine research because of its excellent safety profile and highly efficient recombinant gene expression. Here, we constructed a novel MVA-LMP2A recombinant virus and investigated its specific immune response induction and oncolytic effect. Results: An immunization dose of 2 × 107 PFU induced the highest specific immune response, which was no longer increased by boost injections after four doses. Three weeks post-final immunization, the specific immune response reached its peak. The MVA-LMP2A vaccine-induced LMP2A-specific cytotoxic T lymphocytes (CTLs), which exhibited substantial efficacy against target cells and effectively inhibited tumor growth. Conclusions: Thus, the MVA-LMP2A recombinant virus effectively induces strong LMP2A-specific cellular and humoral immune responses and anti-tumor activity. This work provides a promising therapeutic strategy for developing NPC candidate vaccines, as well as a reference for the treatment of EBV LMP2-associated malignancies.